Implementation of Inverse Document Frequency (TF-IDF) and Cosine Similarity Terms in Determining Research Reviewers for Indonesian Education University Lecturers - Hazmi Ramadhan Adli; M. Munir; Rani Megasari (Universitas Pendidikan Indonesia, 2023)
Research is a mandatory activity for lecturers at the Indonesian Education University. The Institute for Research and Community Service (LPPM) oversees these research activities. Before research can commence, the research proposal must be tested or reviewed by an Examining Lecturer (reviewer). Reviewers are selected based on the similarity between the researcher's and the reviewer's variables and the availability of the reviewer's quota. This selection process utilizes the Term Frequency Inverse Document Frequency (TF-IDF) and Cosine Similarity methods to measure the similarity between queries and documents, specifically abstracts and scientific fields. This approach results in reviewer recommendations with an accuracy of 83.3%, as validated by experts.